Chapter 8 Intergenerational support for autonomous living in a post-socialist housing market Homes, meanings and practices - Druta , Oana (Taylor & Francis, 2019)
This paper explores housing trajectories of young adults and practices of intergenerational support in Romania drawing on narratives of a group of people aged 25-39 living (quasi-) autonomously in Bucharest, and those of kin that support them. It describes three housing arrangements in which family (parental) resources and property play an important role, and argues that in this context of high interdependence, unequal relationships develop between parents and adult children marked by professed entitlement on the part of children and controlling generosity on the part of parents. It shows how interdependent practices of homemaking and material support combine to shape housing trajectories and defi ne the boundaries of ownership over homes that are shared, gifted or given in use within kin networks, sheltering young adults from the vagaries of the market.